Conservation Units in Brazil: a study of case from Region of Cocais, in the East of Maranhão (Research, Society and Development, 2020)
Studies about the difficulties encountered in the creation of Conservation Units in states and municipalities are extremely important. Thus, in this paper, a survey was made of the panorama of conservation units in Brazil and in the Maranhão State, with emphasis on the Cocais Region. The methodological procedures, in the first phase consisted of studying the legislation, the processes related to the creation of conservations units, and in the second, a survey was carried out in the National Register of Conservation Units (CNUC). It was found that Brazil, until the year 2019, has 2,376 conservation units in different categories distributed throughout the national territory, with 1,004 created by the Federal sphere, 1,004 by the States and only 368 by the Municipalities. Of the 2,376 UC's, only 430 (18.1%) have a management plan and 1,946 (81.9%) have not. The Maranhão has 40 conservation units, of which only five have a management plan and none of them is in the Cocais Region. It should be noted that in the Cocais Region there are four Conservation Units: one at the Federal level (Private Reserve of Natural Heritage: Pantanal Farm), one at the State level (Environmental Protection Area: Morro Garapenses) and two at the municipal level: Area Environmental Protection Area and Sucupira Environmental Protection Area. It is noteworthy that the management plans are of fundamental importance for the protection of the conservations units, whether at the national, state and municipal levels. Regarding the Cocais Region, the Management Plan becomes urgent, especially considering that the phytogeography spot has cultural, social and economic value for the local community.